An Error Analysis in Using Present Continuous Tense in Writing Narrative Text - Ratna Dewi Rahmawati; Yon AE Yon AE (Universitas Panca Sakti Bekasi, 2022)
This study aims to find errors in the use of the present continuous tense that are often made by students in class X TKR SMK Teknologi Nasional Bekasi in the 2021/2022 academic year in writing narrative text activities. The researcher employed the descriptive qualitative method in this investigation. The researcher explains the results from the available data. Writing narrative text in the past tense is difficult for 69% of students. 62% of students have difficulty distinguishing the difference between the present and the past tense. Questionnaire data shows that students understand the general structure of narrative texts. And 68% of students have difficulty constructing narrative texts because of their limited knowledge of English. There are four types of errors made by students in writing narrative texts, including errors of omission, errors of addition, errors of misformation, and the last is an error of misordering. The error of misformation was as much as 42%, followed by the error of addition, which was 24%, the error of misordering as much as 22%, and the last error of omission, as much as 12%. This causes them to make mistakes in writing. As a result, they become confused about using tenses or English grammar. This is what causes them to write narrative texts with the wrong choice of tenses